Perceived vs. Verified Cancer Transmission Risk from Deceased Organ Donors in New South Wales (NSW), Australia, 2010-2015 - Hedley, James A; De La Mata, Nicole; Rosales, Brenda M; Waller, Karen M J; Thomson, Imogen K; Kelly, Patrick J; O’Leary, Michael; Cavazzoni, Elena; Wyburn, Kate; Webster, Angela C (International Journal of Population Data Science, 2020)
Introduction Donor suitability assessment is often time-sensitive, with imperfect information available at referral. Opportunities for donation may be missed if donors are rejected based on inaccurate information. Objectives and Approach We sought to compare assessment of cancer transmission risk based on information available at referral (perceived) versus subsequently obtained (verified) detailed medical history, and to identify any missed opportunities for donation. We used data from the NSW Biovigilance Register, a cohort study of deceased organ donor referrals in New South Wales (NSW) 2010-2015. Referrals from NSW who had consent and were otherwise suitable for donation (except for perceived or verified tumour) were analysed. Perceived tumour details were obtained from NSW Organ and Tissue Donation Service referral logs, while verified details were based on the Central Cancer Registry and Admitted Patient Data Collection. Cancer transmission risk was graded using Transplantation Society of Australia and New Zealand guidelines. Results Among 772 referrals otherwise suitable for donation, 601 (78%) had accurately classified cancer transmission risk (κ=0.59). Overall, 53 suitable referrals were rejected due to cancer transmission risk (missed opportunities), including 49 (92%) with overestimated risk (perceived high, verified low/none), and 4 (8%) due to excessive risk aversion (perceived and verified low risk). Missed opportunities had overestimated transmission risk for tumours including leukaemia (8, 16%), lung (8, 16%), melanoma (7, 14%), brain (6, 12%), and breast (6, 12%). Conclusion / Implications Despite time pressure and limited information availability, there is moderate agreement between perceived and verified cancer transmission risk. Nevertheless, improved information availability (e.g. via data linkage) could meaningfully increase the number of actual donors.